Draft Annual Plan 2011-12 Volume-I (Narrative) Government of Rajasthan Planning Department - Planning Commission (Planning Commission, 2011)
The average rainfall is ranging from less than 100 mm. in Jaisalmer to 1000 mm. in Chittorgarh, Jhalawar, Baran and Kota. The average rainfall in western and eastern parts of Rajasthan is 310 mm. and 700. mm respectively. Nearly 90 percent of rains are received in Kharif (June to September). According to Census 2001, population of Rajasthan is 5.65 crore which is 5.49 percent of the country’s total population. During 1991- 2001, the decadal growth rate was 28.41 percent. The population density increased to 165 persons per sq. km. in 2001 from 129 in 1991. Decadal growth in population is higher than the national average. The Scheduled Caste population in the State is 17.2 percent and Scheduled Tribe population is 12.6 percent of the total population.
Narrative
Government of Rajasthan